Understanding leftover consumption through cognitive dissonance theory - Martin, Joshua (2020)
The topic of food waste has been heavily researched over the past several decades because of its numerous negative consequences in a world where resources are finite. Despite the all the attention on the subject, there is not much support showing that this issue is being resolved. Eliminating or even minimising this problem could impact the lives of millions in the United States alone who suffer from food insecurity. As a result, leftover food consumption is analysed as a way of limiting food waste in this study. Leftover consumption was chosen as research supports its connection with reducing food waste. In addition, this topic was analysed through cognitive dissonance theory (CDT) as opposed to behavioural models which frequently appear in this domain. This study is the first in food waste literature to analyse the topic through CDT because it incorporates the subconscious mind which is important for understanding habits and also provides a different way of understanding and affecting behaviour. As a result, it is the purpose of this study to compare attitudes or cognitions related to the consumption of leftover food with frequency of leftover consumption and dissonance reduction modes used. The results from the study will not only provide insight into which factors correlate with leftover consumption but will also detail how cognitive processes justify and affect behaviour. The findings from this study first show that financial considerations are key to younger adults’ decision to consume leftovers. Secondly, the relationship found between level of dissonance and the use of restructuring show support for the use of Leippe & Eisenstadt’s (1999) self-accountability model and efforts influence in dissonance reduction. Lastly, the findings from this study provide justification to analyse behaviour change as dissonance reduction mode in future research on leftover consumption.